(untitled) (Journal of actual problems of jurisprudence, 2025)
The article examines the effectiveness of the structural model of the institution of the Commissioner for Children’s Rights as the most important form of protecting children’s rights and freedoms from violence and exploitation, and examines the experience of the commissioners for children’s rights in foreign countries. Analyzing the 4 models that form the institution of the children’s Ombudsman, the authors identify their positive and negative sides, as well as consider the criteria for the effectiveness of the Commissioner for Children’s Rights. According to the authors, in improving the legal status of the Commissioner for Children’s Rights, it is necessary, firstly, to be regulated at the legislative level and enshrined in constitutional legislation, and secondly, to conduct detailed monitoring of the legislation of the Republic of Kazakhstan in order to identify legal norms that contradict the Constitution of the Republic of Kazakhstan, international standards and modern state priorities. The fact is that the norms of international treaties ratified by the Republic, provided for in article 4 of the Constitution, are practically not implemented. Appropriate monitoring should also be carried out within the framework of bilateral and multilateral treaty obligations ratified by the Republic of Kazakhstan. The formation of the institution of the Commissioner for Children’s Rights makes it possible to eliminate problems that arise in all areas of child protection mechanisms, and also has a positive effect on stimulating the activities of state bodies, local governments and officials. The main goals of the activities of the Ombudsman for Children’s Rights in any country are to defend the needs, rights and interests of minors, to fight for compliance with the Convention on the Rights of the Child, the constitutional rights of children and to promote their dissemination. As the international experience of the Commissioner for Children’s Rights shows, in foreign countries the institution of the Ombudsman for Children’s Rights is defined as "a legally established independent body established to protect the rights and interests of children," and the Institute of the Children’s Ombudsman is recognized as an independent institution for the protection of children’s rights. Keywords: rights of the child, Commissioner for Children’s Rights, convention, model, national law, ombudsman, committee, non-governmental organizations.